Enantioselective Synthesis of β-Nitro Phosphonates Catalyzed by a Secondary Amine Bisthiourea - Nazish, Mohd; Jakhar, Ajay; Gupta, Naveen; Khan, Noor-ul H.; Kureshy, Rukhsana I. (Synlett, 2018)
An enantioselective Michael addition of diphenyl phosphonate to nitroalkenes has been developed by using a secondary amine bisthiourea catalyst to access enantiomerically enriched β-nitro phosphonates. In this reaction, molecular sieves play a key role in achieving high and reproducible yields with a high enantioselectivities of up to 99% at –10 °C. A probable mechanism for the enantioselective Michael addition reaction was established by means of an NMR spectroscopic study.
Keywords: asymmetric synthesis; nitroalkenes; nitro phosphonates; diphenyl phosphonate; organocatalysis; Michael addition